Continuous intravenous infusions of famotidine maintain high intragastric pH in duodenal ulcer. Issue 4 (April 1988) - Merki, H S; Witzel, L; Kaufman, D; Kempf, M; Neumann, J; Röhmel, J; Walt, R P
Abstract : Three double blind crossover studies were carried out to assess the ability of primed infusions of famotidine to raise intragastric pH over 24 hours in 12 duodenal ulcer patients. pH was measured continuously using intragastric electrodes and solid state recording devices. The studies compared the effects of placebo, famotidine 10 mg bolus injection iv followed by continuous infusions of 3.2 mg/h and 4 mg/h in random order. Gastric acidity decreased significantly with both dose regimens (p less than 0.0005) but the effects of either dosage were similar. During fasting median pH rose from 1.35 to 7.1 and 7.05 respectively. During the day, when standard meals were taken, median pH rose from 1.30 to 4.3 and 3.65 respectively. Despite continuous infusions the H2-antagonist was less effective during this time. The latter finding raises questions about gastric secretory control during the day when food is eaten.